Temporal and Spatial Effect of Surrounding Rock and Supporting Construction of a Large Soil Tunnel - Wanjun Ye; Yuntao Wu; Ming Chen; Chong Gao (Advances in Civil Engineering)
Based on the Zaosheng No. 3 tunnel of the Yinchuan-Xi’an high-speed railway, the surrounding rock pressure, contact pressure of the primary support, and secondary lining and internal force of the secondary lining concrete are systematically tested using a vibrating wire sensor, and the correlation between the advance construction distance and the surrounding rock release rate is studied with finite element software. The results show that the pressure on the surrounding rock is low when the deeply buried soil tunnel is excavated and can be divided into three stages: rapid growth, slow growth, and flattening with time. It is more reasonable to calculate the surrounding rock pressure by using tunnel planning calculations. For the contact pressure, although the value of each measuring point in the inverted arch changes a little, the arch pressure obviously has the characteristics of rapid growth and a sharp rebound. Most of the test points of the second lining concrete show a compression state, which is far less than the ultimate compressive strength. At the same time, the initial support of the tunnel bears a large load, while the secondary lining bears a relatively small force, and the load sharing ratio of the two ranges between 0.1 and 0.7; with the progress of the excavation section, the surrounding rock deformation (deformation release rate) increases gradually. When the excavation face is close to the monitoring section, the deformation (deformation release rate) is the most severe. With the increase in the distance between the excavation section and the monitoring section, the deformation (deformation release rate) tends to be flat.